Painting as a Means of Art Therapy for Children – Children with Autism Spectrum Disorder (Case Study in Kaliwungu Kudus State Extraordinary School) - Sutarjo, Johan (CV. Publikasi Indonesia, 2023)
Painting activities can be used as a means of art therapy for children with Autism Spectrum Disorder at the Kaliwungu Kudus State Extraordinary School. The objectives of this study can specifically be formulated: 1). To find out and explain the potential of painting activities for art therapy for children with Autism Spectrum Disorder and 2). To know and explain the implementation of art therapy through painting activities for children with Autism Spectrum Disorder. The benefits of research are generally expected to provide information & input both theoretical and empirical to relevant parties about alternative treatments for the healing process of autistic children through art therapy. In this study, it has used a descriptive study, namely research that has the purpose of describing a situation. This research approach uses qualitative because it examines information, information, & symptoms from a result of the observation process during this study regarding the matter of